Current Surgical Therapy for Bronchiectasis: Surgical Results and Predictive Factors in 86 Patients - Balci, Akin Eraslan; Balci, Tansel Ansal; Ozyurtan, Mehmet Oguzhan (Elsevier Science Inc, 2014)
Background. This study retrospectively evaluated the surgical indications and outcomes of 86 patients with bronchiectasis. Methods. Between 2000 and 2013, the clinical and surgical specifications as well as follow-up results of patients with bronchiectasis were reviewed. Cystic and cylindric morphologic features were determined by chest computed tomography and hemodynamics (perfused and nonperfused), by lung ventilation/perfusion scans. The main indication for surgical resection was localized areas of cystic, nonperfused bronchiectasis. Results. Patients were a mean age of 37.8 +/- 14.5 years. Symptom duration was 43.4 +/- 36.9 months. Bronchiectasis was saccular in 66 patients (76.7%) and varicose in 20 (23.3%). Localized defects were limited in one region of the lung in 53 (61.6%), and 54 (62.8%) showed a mixed or an obstructive ventilatory pattern. Failure of medical therapy was the most common indication for pulmonary resection. The 86 patients underwent 98 operations. Ten underwent staged thoracotomies (contralateral lobectomy, 7; contralateral segmentectomy, 3). Complete resection of all bronchiectatic areas was done in 78 patients (90.7%). Complications developed in 14 patients (14.6%). The mortality rate was 1.1% (n = 1). After surgical treatment, 71 of 86 patients (82.5%) were free of symptoms (excellent), and the remaining 15 (17.5%) had a reduction in preoperative symptoms. The 53 patients with localized perfusion defects underwent complete resection and had symptom-free (excellent) postoperative results. Complete resection independently predicted symptom-free outcome (p < 0.05); a forced expiratory volume in 1 second of less than 60% of the predicted value, an incomplete resection, and a preoperative antibiotic therapy independently predicted postoperative complications (p < 0.05). Conclusions. Bronchiectasis can be improved with operation. In properly selected patients, pulmonary resection can be done with acceptable morbidity and mortality rates and can lead to lasting symptomatic improvements. (C) 2014 by The Society of Thoracic Surgeons
Keywords: Bilateral Bronchiectasis; Management; Surgery